Modification of zeolite Hzsm-5 for methane conversion to higher hydrocarbons - Mat, Ramli (2006)
The direct conversion of methane to liquid hydrocarbon has not yet been successfully economized in an inexpensive process. Acidic zeolites were shown to have reasonable activities for the formation of higher hydrocarbons from methane, however the selectivity was low. The presence of acid sites leads to the oxidation of the higher hydrocarbons formed. Boron incorporation on zeolite would reduce the acidity and thus improved the selectivity. The purpose of this study is to modify the ZSM-5 zeolite with boron and impregnate them with metal for methane conversion. The catalysts were characterized for their structure and acidity. The conversion of methane in the presence of oxygen using packed bed micro reactor has been investigated. Direct substitution of boron for aluminium in the HZSM-5 zeolite structure (BZSM-5), resulted in slightly lower methane conversion (23% compared to 35%) due to its lower acidity, however it improved the higher hydrocarbon selectivity. The introduction of copper species in the catalyst (Cu1%BZSM-5) improved the methane conversion (51%) and the higher hydrocarbon selectivity (11.5%). The effects of operating conditions such as temperature, oxygen concentration, feed flow rate and amount of copper loading on the activity of the catalyst were studied. To examine the importance of further oxidation of intermediate product, the reaction between ethylene and oxygen was carried out using the similar operating conditions with that of methane. The result showed that Cu1%BZSM-5 was capable to convert ethylene to higher hydrocarbons even though it has low acidity. Ethylene conversion and higher hydrocarbon selectivity achieved were 86% and 87% respectively while carbon oxides selectivity was 13%.